2017
DOI: 10.1038/s41598-017-15919-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of reproductive isolation in allopolyploid speciation patterns: empirical insights from the progenitors of common wheat

Abstract: The ability to cause reproductive isolation often varies among individuals within a plant species. We addressed whether such polymorphism influenced speciation of the allopolyploid common wheat (Triticum aestivum L., AABBDD genome) by evaluating the expression of pre-pollination (outcrossing potential) and post-pollination (crossability) barriers in Aegilops tauschii Coss. (the D genome progenitor). In total, 201 Ae. tauschii accessions representing the entire natural habitat range of the species were used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Aegilops tauschii is the easiest species in this genus to utilize in wheat breeding, because there is little to no inhibition to meiotic chromosome pairing with the D genome chromosomes of bread wheat. According to several sources, bread wheat originated about 10,000 years ago (Wang et al, 2013; Matsuoka and Takumi, 2017), which is relatively recent and not long enough for genomic differentiation. Furthermore, Ae.…”
Section: The Use Of Ae Tauschii For Wheat Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Aegilops tauschii is the easiest species in this genus to utilize in wheat breeding, because there is little to no inhibition to meiotic chromosome pairing with the D genome chromosomes of bread wheat. According to several sources, bread wheat originated about 10,000 years ago (Wang et al, 2013; Matsuoka and Takumi, 2017), which is relatively recent and not long enough for genomic differentiation. Furthermore, Ae.…”
Section: The Use Of Ae Tauschii For Wheat Breedingmentioning
confidence: 99%
“…It is important to note that the seed setting rates in F 1 plants also depend on Ae. tauschii accessions (Matsuoka and Takumi, 2017).…”
Section: The Use Of Ae Tauschii For Wheat Breedingmentioning
confidence: 99%
“…Lines of genetic and archeological evidence suggest that the female progenitor of common wheat likely was a free‐threshing cultivar (Matsuoka, 2011). The location in which the original hybridization took place is unknown; however, the southern coastal region of the Caspian Sea is a good candidate based on genetic evidence (Matsuoka & Takumi, 2017; Tsunewaki, 1966; Wang et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…tauschii may have had more opportunities to be involved in the origin of common wheat than others because they frequently hybridized with T. turgidum and because the F 1 hybrids were likely to produce unreduced gametes. In fact, artificial cross-studies have shown that southern Caspian accessions of the TauL2 lineage have a high potential for natural hybridization with T. turgidum (Matsuoka & Takumi, 2017). Thus, the genealogically and geographically structured polymorphism in the crossability with T. turgidum may have had a profound impact on the spatial patterns of common wheat speciation.…”
mentioning
confidence: 99%
“…The Ae. tauschii strains associated with the origin of common wheat are assumed to be the TauL2 lineage [2,17], and only limited reproductive barriers are thought to exist between tetraploid wheat and many of the TauL2 accessions [19]. TauL1 accessions frequently carry a hybrid incompatibility gene, designated Net2 , that triggers low-temperature-induced necrotic cell death upon interspecific hybridization with tetraploid wheat, impeding the generation of synthetic hexaploid wheat [20,21].…”
Section: Introductionmentioning
confidence: 99%